2019
DOI: 10.1111/pops.12567
|View full text |Cite
|
Sign up to set email alerts
|

Anger and Authoritarianism Mediate the Effects of Fear on Support for the Far Right—What Vasilopoulos et al. (2019) Really Found

Abstract: In an important study of popular support for the National Front following the November 13, 2015 terrorist attacks in France, Vasilopoulos, Marcus, Valentino, and Foucault (2019) argue that (1) anger—rather than fear—explains support for the Far Right and (2) the effect of fear on support for the Far Right is negative, rather than positive, as previous work (including my own) would suggest. However, these conclusions are based on statistical models that adjust for anger (but no other emotional variables) when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 27 publications
4
39
0
1
Order By: Relevance
“…Counterintuitively, the present data also indicated a negative relationship between anxiety and RWPP support. This pattern corresponds to an ongoing discussion concerning the role of anger and anxiety on RWPP support (Jost, 2019;Vasilopoulos, Marcus, Valentino, & Foucault, 2019a, 2019b. Contrary to the stable relationship between anger and RWPP support, the present data support different interpretations on the role of anxiety (see Supplementary Materials for additional analysis).…”
Section: Affective Consequences Of Reduced Need Satisfaction and Theisupporting
confidence: 82%
“…Counterintuitively, the present data also indicated a negative relationship between anxiety and RWPP support. This pattern corresponds to an ongoing discussion concerning the role of anger and anxiety on RWPP support (Jost, 2019;Vasilopoulos, Marcus, Valentino, & Foucault, 2019a, 2019b. Contrary to the stable relationship between anger and RWPP support, the present data support different interpretations on the role of anxiety (see Supplementary Materials for additional analysis).…”
Section: Affective Consequences Of Reduced Need Satisfaction and Theisupporting
confidence: 82%
“…We are pleased that John Jost, a valued colleague with a very important contribution in the field of political psychology, has taken an interest in our work and offered an alternative interpretation of our findings (Jost, ). Jost's interpretation rests on two arguments.…”
Section: Claims About Our Model Specificationmentioning
confidence: 95%
“…Exploring what happens when fear increases without simultaneously accounting for the concurrent appraisal of normative violation, expressed by modulating levels of anger, is likely to generate inaccurate estimates of the impacts of fear and anger (Lerner et al, ). Only if affective appraisals were completely orthogonal—or if it could be demonstrated that one affective appraisal causally precedes the other—would it be valid to examine one affective appraisal without the other also being included in the model (on this point, see Jost, ). But the consequence of the appraisal of uncertainty is not so much directed at impacting the substantive decision of what to choose among any visible options but rather to alter how we go about making that choice.…”
Section: A Brief History Of Emotion In Political Science and Psychologymentioning
confidence: 99%